STRUKTUR NARATIF VLADIMIR YAKOVLEVICH PROPP DALAM DONGENG DIE ZERTANZTEN SCHUHE KARYA BRÃœDER GRIMM - PUJI ISTININGDYA PUTRI, KUS; DYAH WOROHARSI PARNANINGRUM, RR (IDENTITAET, 2018)
According to Nurgiyantoro (2005: 200), folktale serves as both a means of entertainment and to pass on the values ??that are believed as truth by the people of the time. Although in recent times folktales have been heavily modified, the characters? actions in the folktale remains unchanged. In narrative structure, a folktale is divided into several sections, however it does not mean that the tale is separated, as it refers to the entirety of the meaning (Endraswara, 2009: 112). Therefore, the research problems in this study are (1) what narrative functions are included in die zertanzten Schuhe by Brüder Grimm, and (2) what spheres of action are included in die zertanzten Schuhe by Brüder Grimm. The objectives of this study are (1) to describe the narrative functions included in die zertanzten Schuhe by Brüder Grimm, and (2) to describe the sphere of action included in die zertanzten Schuhe by Brüder Grimm. This study used the narrative structure theory of Vladimir Yakovlevich Propp. The approach used in this study is descriptive qualitative approach. The sources of data in this study is an electronic book (e-book) which contains a compilation of Brüder Grimm collection tales. While the data in this research is sentences that show the narrative function and sphere of action. Based on the results and discussion on narrative structures in Die zertanzten Schuhe by Brüder Grimm there are 17 functions found and those are difficult task (M), lack(a), ?the first function of the donor? (D), interdiction (?), provision or receipt of magical agent (F) ?heros reaction (E), ?departure? (?), ?transfiguration? (T), trickery? (?), ?mediation, the connective incident? (B), ?the initial misfortune or lack is liquated? (K), ?reconnaissance? (?), ?branding? (J), ?return (?), solution (N), wedding (W), and ?punishment? (U). From those functions, there are six spheres of actions that were found 6 in die zertanzten Schuhe by Brüder Grimm, namely hero, helper, donor, villain, princess and her father, and dispatcher. Keyword : narrative Structure, folktale, Brüder Grimm